2011
DOI: 10.1007/s12195-011-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Focal Adhesion Instability and Cell Reorientation Under Cyclic Substrate Stretching

Abstract: Associate Editors Mian Long and Fan Yuan oversaw the review of this article.Abstract-The adhesion-based cell mechanosensitivity plays central roles in many physiological and pathological processes. Recently, quantitative understanding of cell responses to external force has been intensively pursued. However, the frequency dependent cell responses to the substrate stretching have not yet been fully understood. Here we developed a multiscale modeling framework for studying cell reorientation behaviors under subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…The Young's modulus, Poisson's ratio, and prestrain of the cell layer are denoted by E c , n c , and ε 0 , respectively. The magnitude of the prestrain, ε 0 , is thought to be~0.1 under physiological conditions (43)(44)(45). The two-dimensional plane stress constitutive relation of the cell layer is written as…”
Section: Theoretical and Numerical Modelingmentioning
confidence: 99%
“…The Young's modulus, Poisson's ratio, and prestrain of the cell layer are denoted by E c , n c , and ε 0 , respectively. The magnitude of the prestrain, ε 0 , is thought to be~0.1 under physiological conditions (43)(44)(45). The two-dimensional plane stress constitutive relation of the cell layer is written as…”
Section: Theoretical and Numerical Modelingmentioning
confidence: 99%
“…Recently, Kong et al (2010) presented a microscopic mechanochemical coupling model to investigate the stabilizing to disruptive transition of an individual FA modulated by cellular forces. Zhong et al (2011) studied the dependency of stretching forceinduced cell reorientation on loading frequency. Additionally, Huang et al (2011) developed a mechano-chemical model for elucidating the impact of substrate rigidity on cell adhesion strength.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic properties of SFs, such as pre-tension, viscoelastic relaxation, and motor-force homeostasis, are crucial to the mechanosensitive responses of cells to mechanical stimuli (23,78,114,121,157). It has been found that well-spread cells exert tension on their surroundings (35), which is caused mostly by the contractility of SFs.…”
Section: Stress Fibersmentioning
confidence: 99%